Magnetic resonance imaging, magnetisation transfer imaging, and diffusion weighted imaging correlates of optic nerve, brain, and cervical cord damage in Leber's hereditary optic neuropathy. Issue 4 (1st April 2001) - Inglese, M; Rovaris, M; Bianchi, S; Mantia, L La; Mancardi, G L; Ghezzi, A; Montagna, P; Salvi, F; Filippi, M
Abstract : OBJECTIVES: Leber's hereditary optic neuropathy (LHON) is a mitochondrial disease leading to bilateral loss of central vision and severe optic nerve atrophy. A subtype of LHON presents additional clinical and MRI aspects indistinguishable from those of multiple sclerosis (MS) (LHON-MS). In patients with LHON or LHON-MS, an assessment was made of ( a ) the severity of optic nerve damage, using MRI and magnetisation transfer imaging (MTI), and ( b ) the presence and extent of macroscopic and microscopic pathology in the brain and cervical cord, using MRI and MT ratio (MTR) and mean diffusivity ( D̄ ) histogram analysis. METHODS: Ten patients with LHON, four with LHON-MS, and 20 age and sex matched healthy controls were studied. For the optic nerve and the brain, dual-echo turbo spin echo (TSE), T1 weighted spin echo, and MT images were obtained. For the brain, fast fluid attenuated inversion recovery (fast FLAIR) and diffusion weighted images were also obtained. For the cervical cord, fast short tau inversion recovery (STIR) and MT images were obtained. The volume and the average MTR value of both the optic nerves were measured. MTR and D̄ histograms of the normal appearing brain tissue (NABT) and MTR histograms of the whole cervical cord tissue were created. RESULTS: The mean values of optic nerve volumes and MTR were significantly lower in patients with LHON than in healthy controls. Mean NABT-MTR histogram peak height was significantly lower in patients with LHON than in controls, whereas no significant difference was found for any of the cervical cord MTR histogram derived measures. Average diffusivity (D̄ ) was higher in patients with LHON than in controls. Optic nerve volume and MTR value and mean NABT-MTR were lower in patients with LHON-MS than in those with LHON. CONCLUSIONS: The severity of optic nerve pathology in LHON is measurable in vivo using MRI and MTI. MTR and D̄ histogram analysis suggests that microscopic brain damage occurs in LHON and that it is more severe in the MS-like form of the disease.